2013
DOI: 10.1590/s2317-15372013000100012
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of silicon and the effect on wheat seed yield and quality

Abstract: -Adequate nutrients for plants are important for increasing the yield and quality of the seeds produced. The objective of this study was to evaluate foliar fertilization with silicon in wheat and its effect on seed yield and physiological quality. Treatments consisted of two silicon dosages (three and six liters silicon per hectare) and the control (no silicon) and five wheat cultivars: OR "Quartzo", OR "Ônix", Fundacep "Linhagem", Fundacep "Campo Real" and Fundacep "Horizonte". The experimental design was ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
2
8
0
1
Order By: Relevance
“…Also tests presented by [10] confirmed a beneficial effect of root and foliar application of silicon to wheat plants. The presented results also confirm theirs findings, however the research conducted by Segalin et al [22] revealed that foliar application of silicon did not affect yield nor physiological quality of wheat seeds of different cultivars. In other crops beneficial effect of silicon also was indicated, the obtained results by Artyszak et al [2] demonstrated that the use of the environmentally safe calcium and silicon foliar fertilizer (Herbagreen basic) is advantageous for the sugar beet production.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Also tests presented by [10] confirmed a beneficial effect of root and foliar application of silicon to wheat plants. The presented results also confirm theirs findings, however the research conducted by Segalin et al [22] revealed that foliar application of silicon did not affect yield nor physiological quality of wheat seeds of different cultivars. In other crops beneficial effect of silicon also was indicated, the obtained results by Artyszak et al [2] demonstrated that the use of the environmentally safe calcium and silicon foliar fertilizer (Herbagreen basic) is advantageous for the sugar beet production.…”
Section: Discussionsupporting
confidence: 91%
“…In this way plants gain the ability to respond earlier and more efficiently to a pathogen or insect attack [13,15]. Application of soluble form of Si can reduce severity of plant diseases [20,22]. According to Griffin et al [9] Si reduces slug feeding on wheat seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…Control non-fertilized seeds were commonly attacked by fungi of Alternaria and Septoria genera, and this indicated a positive effect of silicon on seed condition. However, the research by Segalin et al [57] revealed that foliar application of silicon did not affect either yield or physiological quality of wheat seeds of different cultivars.…”
Section: Discussionmentioning
confidence: 92%
“…Yu and Gao ( 2012 ) investigated the effects of Si on the yield of two wheat cultivars and found that appropriate Si levels could increase the grain yield of wheat, and the increase resulted from the increase in spike number and grain number per spike. By contrast, Segalin et al ( 2013 ) tested the effect of foliar applications of Si on wheat yield and quality and did not observe any improvement in fi ve cultivars. This may be related to the fact that foliar applications did not lead to Si accumulation in wheat as reported by Guével et al ( 2007 ).…”
Section: Wheatmentioning
confidence: 88%